ψ1 - Operator Generated by Fuzzy Filter - Najm , Mohammed Majid; AL-Swidi, Luay A. (International Journal of Psychosocial Rehabilitation, 2020)
In these paper we presented a new concept via fuzzy positional function properties were obtained and examples were provided to clarify these properties.